Expression of mutant p53 protein in hepatocellular carcinoma. Issue 1 (January 1994) - Collier, J D; Carpenter, M; Burt, A D; Bassendine, M F
Abstract : p53 mutations are a common genetic finding in hepatocellular carcinoma from areas of high aflatoxin exposure. Recent small studies have shown that p53 gene mutations may be less common in areas with a low prevalence of hepatocellular carcinoma such as Great Britain. The protein product of mutant p53 can be detected immunohistochemically because of its longer half life in comparison with native protein. This study used a novel monoclonal antibody DO-7, raised against recombinant p53 and effective in routinely processed biopsy specimen tissue, to detect the mutant protein in a series of 45 cases of hepatocellular carcinoma occurring in white subjects resident in the United Kingdom. Focal nuclear labelling was seen in four cases (9%); surrounding cirrhotic tissue in one of these was negative for p53 expression. This study shows that p53 mutations are a rare event in hepatocarcinogenesis in Great Britain, an area of low aflatoxin exposure, and supports the concept of geographical variations in the cause and pathogenesis of hepatocellular carcinoma.